Pengaruh Latihan Imagery terhadap Penurunan Kecemasan Bertanding Klub Futsal Keramat FC - Qennes, Dhyo; Agus Sulastio; Wedi S (Journal Sport Science Indonesia, 2025)
Futsal is a ball game played by two teams, each consisting of five players, with the goal of scoring into the opponent's net. This game can trigger competition anxiety due to the pressure to score goals, intense competition, and individual and team expectations in a fast-paced match situation. This study aims to determine the level of competition anxiety among Keramat FC futsal players before and after imagery training and to examine the differences in competition anxiety before and after the training. This study adopts a Pretest-Posttest Control Group Design. The experimental research was conducted using a pre-test and post-test approach. The research population consists of 26 athletes from the Keramat FC Futsal Club, using a total sampling method. The sample was divided into 13 players in the experimental group and 13 players in the control group. The data analysis technique used in this study is the t-test formula. The results indicate that before imagery training, most players' competition anxiety levels were in the high category, whereas after imagery training, most players' anxiety levels fell into the normal category. The t-test results showed a t-value of 10.809 > t-table value of 2.064, meaning t-value > t-table, leading to the conclusion that Ho is rejected and Ha is accepted. This confirms that imagery training has a significant effect on reducing competition anxiety in Keramat FC Futsal Club in 2024.